If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8r = 15 + 3r Solving 8r = 15 + 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. 8r + -3r = 15 + 3r + -3r Combine like terms: 8r + -3r = 5r 5r = 15 + 3r + -3r Combine like terms: 3r + -3r = 0 5r = 15 + 0 5r = 15 Divide each side by '5'. r = 3 Simplifying r = 3
| (2x^2+x+9)+(3x^2-4x-5)= | | 2x-1/4x-1 | | b^2+2b-180=0 | | 2/7z=8 | | y-21.95=-13.95 | | (3x-6)+7=2x+8 | | 2X*Y=1000 | | X^2-y^2-4x+4=0 | | (35x80)/100= | | w^2+w-45=0 | | 3x-13=6x-4 | | 4V=42-2V | | 2x+10=10x-4 | | -2y/2=8-3x/2 | | 2/3(9x-12)=24 | | 2L+2(10)=60 | | f(x-1)=4x^2+5x+7 | | X+3x-1=33 | | 16+7c=51 | | x^2+.12x-.054=0 | | 2w=2.56 | | -28+p=(p-10) | | -26/50 | | 22x-3.5=18.5 | | y+6(y-9)= | | y=41x-(88000+33x) | | 7x+6x+3+8=10x+5+2x | | 13x+.64x=100 | | 6x-14-4x=6x-9 | | (4X+7)+(2X-16)= | | 7(4y-9)-(2y+6)= | | 3y-10=x |